Low admission Norton scale scores are associated with falls long after rehabilitation in the elderly with hip fractures - Halperin E (Dove Medical Press, 2012)
Ehud Halperin,1 Tal Engel,2 Shany Sherman,2 Dan Justo2,31Department of Internal Medicine D, Sourasky Medical Center, Tel-Aviv, 2Department of Internal Medicine E, Sheba Medical Center, Tel-Hashomer, 3Department of Geriatrics, Sourasky Medical Center, Tel-Aviv, IsraelBackground: In this study, we investigated if low admission Norton scale scores (ANSS) are associated with falls, fractures, hospitalizations, and death, after rehabilitation in the elderly with hip fractures.Methods: This prospective historical study followed consecutive elderly patients (≥65 years) who were admitted for rehabilitation following hip fracture surgery during 2009 and followed up in January or February 2012. The incidence of falls, number of falls, incidence of fractures, number of hospitalizations, and death rates were compared between patients with low (≤14) and high (≥15) ANSS.Results: The final cohort included 174 patients of mean age 83.6 ± 6.2 years, with 133 (76.4%) being women. Fifty-seven (27.0%) patients died during follow-up. Of the remaining 127 patients, 44 (34.6%) fell at least once and 15 (11.8%) suffered fractures. Overall, 81 (46.6%) patients had a low ANSS. Relative to patients with a high ANSS, they had a higher incidence of falls (odds ratio 3.3, 95% confidence interval 1.5–7.1; P = 0.002) and fell more times (1.2 ± 1.8 versus 0.6 ± 1.7; P = 0.002). Regression analysis showed that ANSS (as a parametric variable) as well as a low ANSS (as a nonparametric variable) were independently associated with falls (P = 0.002 and P = 0.009, respectively). There were no differences between patients with low and high ANSS in terms of incidence of fractures, number of hospitalizations, and death rates.Conclusion: The Norton scoring system may be used for predicting falls long after rehabilitation in the elderly with hip fractures.Keywords: falls, hip fracture, Norton scale, rehabilitation